2003
DOI: 10.1016/s0960-9822(02)01359-3
|View full text |Cite
|
Sign up to set email alerts
|

Naip5 Affects Host Susceptibility to the Intracellular Pathogen Legionella pneumophila

Abstract: We conclude that polymorphisms in Naip5 are involved in the permissiveness differences of mouse macrophages for intracellular Legionella replication. We speculate that Naip5 is a functional mammalian homolog of plant "resistance" proteins that monitor for, and initiate host response to, the presence of secreted bacterial virulence proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(216 citation statements)
references
References 44 publications
6
207
0
3
Order By: Relevance
“…Intracellular growth was quantified by plating appropriately diluted (Yamamoto et al, 1988). However, bone-marrow-derived macrophages from BALB/c mice permit the intracellular replication of L. pneumophila (Wright et al, 2003), which corresponds to the observed permissiveness of RAW264.7 macrophages.…”
Section: Methodsmentioning
confidence: 82%
“…Intracellular growth was quantified by plating appropriately diluted (Yamamoto et al, 1988). However, bone-marrow-derived macrophages from BALB/c mice permit the intracellular replication of L. pneumophila (Wright et al, 2003), which corresponds to the observed permissiveness of RAW264.7 macrophages.…”
Section: Methodsmentioning
confidence: 82%
“…The possibility of a cooperative interaction between Ipaf and Naip5 has been investigated thoroughly in L. pneumophila infections, which we have recently reviewed in detail (4). Briefly, several lines of indirect evidence have suggested that Ipaf and Naip5 act in concert: (i) Ipaf and Naip5 coimmunoprecipitate in overexpression assays (9,11), (ii) both Ipaf and Naip5 are L. pneumophila susceptibility genes in vitro in macrophages and in vivo in mice (6,7,9,13), and (iii) both Ipaf and Naip5 modulate caspase 1 activity (5,9). Other data indicate that Naip5-deficient macrophages retain their ability to activate caspase 1 and IL-1␀ secretion in response to L. pneumophila (8,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Nalp3 activates caspase 1 via a pyrin domain, but does so by using the adaptor protein ASC to recruit caspase 1 (3). The NLR Naip5 was identified as the Legionella pneumophila susceptibility locus in A/J mice (6,7). Because Ipaf also provides resistance to L. pneumophila infection and Ipaf and Naip5 have been shown to interact with each other in overexpression assays, it has been suggested that the two work in concert to activate caspase 1 (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…19 NAIP was the first mammalian IAP to be discovered, but rather than having a role in regulation of cell death, it is a 44,45 that appears to function in providing innate immunity to infection by bacteria such as Leigonella pneumophila. 46,47 Although some initial reports suggested it might be able to inhibit caspases in vitro, subsequent studies have shown NAIP cannot directly inhibit caspases at physiological concentrations. 29 Similarly, although Survivin, an IAP that acts together with aurora kinase B and the inner centromere protein during mitosis, was initially proposed to inhibit caspases, 48 it is no longer thought to be able to do so.…”
Section: Iapsmentioning
confidence: 99%